Design Computer Applications For Analyzin Community Education Foundation Teacher Performance In Langkat District - A Hamid Fahmie (International Journal of Economics, Business and Innovation Research, 2024)
The Community Education Foundation is a philanthropic organization that focuses on the education sector, namely providing support to high schools and vocational institutions. In the context of vocational and high school education, there exists a daily exchange of knowledge and skills between teachers and students through the process of teaching and learning. One of the assets of a school is its ability to produce graduates who are capable of competing, either by pursuing further education or by utilizing the information they have acquired throughout their schooling. The primary determinant for producing high-quality graduates is the active participation of teachers in the learning process, together with other supplementary elements. Thus, in order to improve the caliber of educators, this organization has carried out evaluations and assessments at the schools it provides assistance to. The assessment procedure evaluates the efficacy of instructors in carrying out their responsibilities. However, prior deployments have shown that conducting assessments and evaluations necessitates a significant amount of time for data processing. This leads to decreased efficiency in these operations. To address this scenario, we developed an application with the aim of streamlining and enhancing the precision of computations. We developed a computer program, referred to as software, with the purpose of evaluating and assessing the effectiveness of teachers. We conduct data analysis on the questionnaire responses of teacher performance indicators by delivering an average exam. Out of the 32 teachers, 8 of them, which is 25% of the total, did better than the average. By analyzing the results of the average exam, you may make informed assessments of the teacher’s performance, which can be valuable for future decision-making.